2004
DOI: 10.1037/0021-9010.89.4.730
|View full text |Cite
|
Sign up to set email alerts
|

Union Commitment and Participation: A 10-Year Longitudinal Study.

Abstract: The authors longitudinally investigated the causal nature of the relationship between union commitment and participation in informal union activities. A total of 134 members of the National Association of Letter Carriers were studied over a 10-year period. Using cross-lagged regression analysis, early union commitment was found to predict the level of informal union participation 10 years later. The reverse and reciprocal relationships were not supported. These findings support and extend earlier research on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 41 publications
9
86
0
Order By: Relevance
“…Furthermore, we expect that the relationships between the aforementioned explanatory variables (i.e., felt obligation to the union, trust in the union, and union-based self-esteem) and union citizenship behaviors will be mediated by union commitment. Union commitment is generally considered to be the best predictor (i.e., most proximal) of union-supportive behavior and research has confirmed a consistently strong relationship between these two variables (Bamberger et al 1999;Fullagar et al 2004;Fuller and Hester 1998).…”
Section: Covenantal Relationshipsmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we expect that the relationships between the aforementioned explanatory variables (i.e., felt obligation to the union, trust in the union, and union-based self-esteem) and union citizenship behaviors will be mediated by union commitment. Union commitment is generally considered to be the best predictor (i.e., most proximal) of union-supportive behavior and research has confirmed a consistently strong relationship between these two variables (Bamberger et al 1999;Fullagar et al 2004;Fuller and Hester 1998).…”
Section: Covenantal Relationshipsmentioning
confidence: 93%
“…Accordingly, union citizenship behaviors (UCB's) are voluntary and contribute to the union's functions, but are not explicitly required or rewarded by the union. Due to the discretionary nature of union citizenship behaviors and the low expectations of associated economic rewards, researchers have generally focused on social exchange (Fullagar et al 2004) or psychological exchange (Kelloway et al 2000) theories to identify factors that increase union citizenship behavior. However, organizational citizenship behavior research suggests that social and psychological exchange theories offer an incomplete view of the factors involved in "active citizenship" (Van Dyne et al 1994: 768).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on union commitment (Gordon et al . 1980) shows that the greater the commitment, the greater the actual participation and activism (Fullagar et al . 2004).…”
Section: Cultivating Social Commitmentmentioning
confidence: 99%
“…In general terms, this stream of literature identifies two types of member commitment to their unions, a calculative‐based commitment and value‐based commitment (Bamberger and Kluger 1999; Sverke and Kuruvilla 1996). Member commitment to unions is a function of several variables, including beliefs about unionism, socialization and job satisfaction (see Fullagar et al. 2004 for a review), but it is the consequences of union commitment that are more germane here.…”
Section: Linkages Between Member Activism and Union Renewalmentioning
confidence: 99%